Evolución de los servicios de transporte y seguros internacionales de bienes entre Colombia y los Estados Unidos de América (2023)
This research is a compilation of several compounds that aims to analyze the evolution of goods transport services and international insurance with the United States of America. Services are an important part of the economy of each country and the main component of international trade, in this way a wide expansion is generated in the tertiary sector, generating evolution and changes in international transport and insurance services incorporating new technologies that contribute to the continuous and improved development so that the economy is dynamic and competitive.